Explaining Interest Rate Decisions When the MPC Members Believe in Different Stories - Carl Andreas Claussen; Øistein Røisland (Norges Bank, 2013)
Modern central banks do not only announce the interest rate decision, they also communicate a "story" that explains why they reached the particular decision. When decisions are made by a committee, it could be difficult to find a story that is both consistent with the decision and representative for the committee. Two alternatives that give a unique and consistent story are: (i) vote on the interest rate and let the winner decide the story, (ii) vote on the elements of the story and let the interest rate follow from the story. The two procedures tend to give different interest rate decisions and different stories due to an aggregation inconsistency called the "discursive dilemma". We investigate the quality of the stories under the two approaches, and find that alternative (ii) gives stories that tend to be closer to the true (but unobservable) story. Thus, our results give an argument in favour of premise-based, as opposed to conclusion-based, decisionmaking.
hdl:11250/2496702
Keywords: E52; E58; D71; 330; monetary policy committees; communication; judgment aggregation; discursive dilemma